A 3D-printed, high-strength, and drug-eluting composite for the treatment of periprosthetic joint infections - Abar, Bijan; Goonewardene, Harrison; Sheng, Richard; Negus, Mitchell H.; Allen, Nicholas B.; Kelly, Cambre N.; Stinson, Natasha C.; Becker, Matthew L.; Thaden, Joshua T.; Adams, Samuel B.; Gall, Ken (Frontiers in Biomaterials Science, 2025)
IntroductionPeriprosthetic joint infections are relatively rare complications of total joint replacements. The standard of care for these infections involves the placement of a temporary spacer made of poly (methyl methacrylate) (PMMA) bone cement combined with antibiotics. The rate of major complication can be as high as 12% for PMMA spacers. Therefore, this study was designed to identify an alternative resin material that could be 3D printed, provide mechanical support necessary for ambulation, and deliver a therapeutic dose of antibiotics over an extended period.MethodsTest substrates were photochemically printed out of Biomed Clear (BMC) loaded with up to 16% gentamicin or 10% vancomycin (wt%). PMMA and BMC composites were characterized using differential scanning calorimetry, dynamic mechanical analysis, compression testing, and a 30-day antibiotic elution study.ResultsThe thermoset properties of the BMC allowed for the compressive properties to remain unchanged (post-elution = compressive strength 84–94 MPa) as antibiotics were added to the resin (0–16 wt%). However, antibiotic elution was influenced by the type and concentration of the antibiotic in the composite. In contrast, the thermoplastic properties of PMMA led to a decrease in compressive properties with the addition of antibiotics, but PMMA was able to elute relatively more antibiotics.DiscussionThis study described a novel method to 3D print load bearing materials that can release antibiotics over 30 days. BMC composites have some advantages and disadvantages compared to PMMA that need to be considered when developing new treatments for orthopaedic infections.